What is a capable guardian to older fraud victims? Comparison of younger and older victims’ characteristics of online fraud utilizing routine activity theory - Parti, Katalin (Frontiers in Psychology, 2023)
Objective The paper compares victim group characteristics: we test routine activities theory to compare the differences in online fraud vulnerabilities of victims aged 18–54 and victims of 55 and above. Methods/sample A representative sample of US citizens 18 and above was collected in October 2020. Victims under 55 encompassed 35.3% (n = 915), victims 55 and above 12.9% (n = 334) of the total sample (n = 2,589). We utilized non-parametric statistical methods for testing whether older and younger victims’ characteristics can be derived from the same independent variables. Results Computer time, computer familiarity, and technical guardians determine online victimization in older individuals, similarly to younger age groups. However, older victims differ in characteristics from younger victims. Seniors were less likely to apply technical guardians such as camera cover, identity theft monitoring, and credit card freeze, even after experiencing online scams. Being a single parent was a protective factor for older individuals, but having a full-time job made older individuals more prone to experience online fraud victimization compared to being retired. In addition, older victims were less likely to report scams than younger ones. Conclusion/implications Although this research found significant differences between older and younger fraud victims’ characteristics, target suitability and capable guardianship must be further investigated and conceptualized when applying routine activities theory for online fraud against older people.